A β-Lactamase Based Reporter System for ESX Dependent Protein Translocation in Mycobacteria - Rosenberger, Tobias; Brülle, Juliane K.; Sander, Peter (PLOS ONE, 2012)
Protein secretion is essential for all bacteria in order to interact with their environment. Mycobacterium tuberculosis depends on protein secretion to subvert host immune response mechanisms. Both the general secretion system (Sec) and the twin-arginine translocation system (Tat) are functional in mycobacteria. Furthermore, a novel type of protein translocation system named ESX has been identified. In the genome of M. tuberculosis five paralogous ESX regions (ESX-1 to ESX-5) have been found. Several components of the ESX translocation apparatus have been identified over the last ten years. The ESX regions are composed of a basic set of genes for the translocation machinery and the main substrate - a heterodimer. The best studied of these heterodimers is EsxA (ESAT-6)/EsxB (CFP-10), which has been shown to be exported by ESX-1. EsxA/B is heavily involved in virulence of M. tuberculosis. EsxG/H is exported by ESX-3 and seems to be involved in an essential iron-uptake mechanism in M. tuberculosis. These findings make ESX-3 components high profile drug targets. Until now, reporter systems for determination of ESX protein translocation have not been developed. In order to create such a reporter system, a truncated β-lactamase (‘bla TEM-1) was fused to the N-terminus of EsxB, EsxG and EsxU, respectively. These constructs have then been tested in a β-lactamase (BlaS) deletion strain of Mycobacterium smegmatis. M. smegmatis ΔblaS is highly susceptible to ampicillin. An ampicillin resistant phenotype was conferred by translocation of Bla TEM-1-Esx fusion proteins into the periplasm. BlaTEM-1-Esx fusion proteins were not found in the culture filtrate suggesting that plasma membrane translocation and outer membrane translocation are two distinct steps in ESX secretion. Thus we have developed a powerful tool to dissect the molecular mechanisms of ESX dependent protein translocation and to screen for novel components of the ESX systems on a large scale.